Ancient Tamil inscription recognition using detect, recognize and labelling, interpreter framework of text method - Balasubramanian Murugan; P. Visalakshi (Heritage Science)
Abstract Tamil is the oldest language spoken in Tamil Nadu, India, with inscriptions dating back to the third century BCE found in caves, temples, and archaeological sites. The style and content of these inscriptions have evolved over time, reflecting changes in society, governance, and language usage. They provide valuable insights into rulers, dynasties, administrative systems, religious practices, and societal norms of their era. However, the diverse fonts and styles of these inscriptions necessitate an efficient method for alphabet and word recognition. Existing algorithms primarily recognize Tamil words and characters from the nineteenth century and do not address the language and styles used in the third century. This study proposes a novel DR-LIFT framework specifically designed for recognizing Tamil inscriptions from this earlier period, overcoming the limitations of current methods. The dataset used consists of third-century Tamil inscriptions. The algorithms within the DR-LIFT method specifically designed to detect text with intricate features such as curves, loops, and lines, significantly enhancing detection accuracy. The proposed framework achieves impressive outcomes, with a recognition accuracy of 99% and a recognition rate of 98.8%.